Rectal epithelial cell proliferation patterns as predictors of adenomatous colorectal polyp recurrence. Issue 4 (April 1993) - Anti, M; Marra, G; Armelao, F; Percesepe, A; Ficarelli, R; Ricciuto, G M; Valenti, A; Rapaccini, G L; De Vitis, I; D'Agostino, G
Abstract : To determine whether proliferative patterns in flat rectal mucosal samples can predict the recurrence of adenomatous colorectal polyps, after polypectomy, biopsy specimens from normal looking rectal mucosa were obtained at endoscopy from 55 patients diagnosed for the first time as having adenomatous colorectal polyps. Epithelial cell proliferation was assessed in biopsy specimens through 3H-thymidine autoradiography. After polypectomy, patients were followed for 24 months and underwent complete colonoscopy every 6 months to detect and remove any metachronous lesions. In 40 patients second biopsy specimens were taken during one of the follow up colonoscopies to evaluate the stability of proliferative indices over time. The ratio of labelled (S phase) to total cells (labelling index) for the entire crypt, as well as ratios for each of the five equal compartments into which the crypt had been divided longitudinally, was calculated for each patient. Mean labelling indices for upper crypt compartments 3 and 4 + 5 in the 22 patients in whom polyps recurred were significantly higher (respectively p < 0.05 and p < 0.01) than those of the 33 without recurrence suggesting that an upward shift of the crypt's replicative compartment is associated with polyp recurrence. Labelling indices remained essentially unchanged in those patients who underwent biopsy twice. Reproducible kinetic parameters such as these might be useful in planning follow up of patients with adenomatous polyps after polypectomy.